Progress and prospects of polysaccharide-based nanocarriers for oral delivery of proteins/peptides. (15th July 2023) - Yuan, Haoyang; Guo, Chen; Liu, Lei; Zhao, Linxuan; Zhang, Yu; Yin, Tian; He, Haibing; Gou, Jingxin; Pan, Bochen; Tang, Xing
Abstract: The oral route has long been recognized as the most preferred route for drug delivery as it offers high patient compliance and requires minimal expertise. Unlike small molecule drugs, the harsh environment of the gastrointestinal tract and low permeability across the intestinal epithelium make oral delivery extremely ineffective for macromolecules. Accordingly, delivery systems that are rationally constructed with suitable materials to overcome barriers to oral delivery are exceptionally promising. Among the most ideal materials are polysaccharides. Depending on the interaction between polysaccharides and proteins, the thermodynamic loading and release of proteins in the aqueous phase can be realized. Specific polysaccharides (dextran, chitosan, alginate, cellulose, etc.) endow systems with functional properties, including muco-adhesiveness, pH-responsiveness, and prevention of enzymatic degradation. Furthermore, multiple groups in polysaccharides can be modified, which gives them a variety of properties and enables them to suit specific needs. This review provides an overview of different types of polysaccharide-based nanocarriers based on different kinds of interaction forces and the influencing factors in the construction of polysaccharide-based nanocarriers. Strategies of polysaccharide-based nanocarriers to improve the bioavailability of orally administered proteins/peptides were described. Additionally, current restrictions and future trends of polysaccharide-based nanocarriers for oral delivery of proteins/peptides were also covered. Graphical abstract: Unlabelled Image